Estudo de caso sobre transferências logísticas, com a utilização de veículos semirreboque de duplo piso - Oliveira, Rafael Jesus de (2015)
The purpose of this dissertation is to analyze the use of semi-trailer vehicles with single and double floors process transfers and transshipments, common in logistics operations when they have more than one distribution center or industrial complex. These different manifestations contribute very little to the final value of the product, and is characterized by a high cost to organizations, resources aimed at reducing costs or increasing efficiency should be the subject of academic studies. To this end the research approaches in a comparative way the two models, with quantitative data obtained in a company that uses the two models presented trough case study in order to explore the pattern of transshipment and drives.